Labour income inequality and the informality sector in Colombian cities - Ariza, John (2017)
Labour markets in developing countries are crucial to determine income inequality. In this paper, we use a panel data approach to study the effect of the informal sector on labour income inequality for thirteen cities in Colombia from 2002-2015. We use the rate of underemployment, the average duration of unemployment and the intensity of forced migration from armed conflicts as instruments for the urban informal sector. Results suggest that the informal sector has a positive and statistically significant effect on labour income inequality, which implies that an increase by one percentage point in the informal sector increases the Gini coefficient of labour income by about 0.07.